A prospective open-label study of home use of mifepristone for medical abortion in Nepal. Issue 3 (March 2015) - Conkling, Kathryn; Karki, Chanda; Tuladhar, Heera; Bracken, Hillary; Winikoff, Beverly
Abstract Objective To assess the uptake and acceptability of self-administration of mifepristone at home for medical abortion in Nepal. Methods A prospective, comparative, non-randomized, open-label study was conducted at two hospitals in Kathmandu, Nepal, between November 11, 2009, and January 15, 2011. All women in good health and aged 18 years or older who sought medical abortion after fewer than 64 days of pregnancy were enrolled. Participants were offered the choice of taking 200 mg mifepristone orally in the clinic or at home; all participants self-administered 400 μg of sublingual misoprostol at home 24–72 hours later. All participants were scheduled to return to the clinic within 14 days of mifepristone administration for follow-up. Results Among 200 participants, 144 (72.0%) opted to take the mifepristone at home. Medical abortion was successful in 130 (95.6%) of 136 women in the home group who were followed up and 53 (94.6%) of 56 women in the clinic group. Only 4 (2.9%) women in the home group took the mifepristone after the scheduled time. Overall, 133 (97.8%) women in the home group stated that they would recommend home administration of mifepristone if a friend wanted a medical abortion. Conclusion Self-administration of mifepristone outside the clinic should be offered to all women as part of routine medical abortion services in Nepal. Clinical trials.gov: NCT00994734 .